Sedimentology of the lower Uitenhage Group in the Middle to Late Mesozoic Oudtshoorn Basin, South Africa - Dinis,Yambi Renato Daniel (Department of Geological Sciences, 2019)
The Oudtshoorn Basin is the largest onshore Mesozoic depocentre along the southern margin of South Africa, and is among the sedimentary basins that have been linked to the break-up of southern Gondwana. Filled by the continental lower Uitenhage Group, which for the most part is sparsely fossiliferous, difficult to correlate on a regional scale and void of non-renewable natural resources, the Oudtshoorn Basin is relatively poorly studied. This project aims at carrying out an in depth, field- and lab-based investigation of the sediment supply processes and directions, location of sediment sources and palaeoclimate during the deposition of the lower Uitenhage Group in the Oudtshoorn Basin. In addition to the sediment transit patterns from source to sink via palaeocurrent measurements and petrographic studies, the sedimentary architecture was assessed via modern facies analysis techniques, which also permitted the investigation of the reason, the nature and the mode of sediment transport (traction currents vs. mass movements) in the early stages of Gondwana fragmentation. The study identified nine facies associations, the composition, clast size and orientation of which suggest steep vs. gentle gradients along the northern and southern basin margins, respectively, and very gentle gradients in the basin centre. Furthermore, the common mass movement-deposits in the north contrast the sediments laid down by traction current and in turbid waters in the south, southwest, west and centre of the basin. Sediments were sourced from the northern and southern margins in alluvial fans, and moved toward the centre, where axial fluvial system dominated. Sedimentary facies distribution, grain size, and petrological composition collectively indicate sediment transport distances that were shorter and more rigorous in the north than in the south. Geochemical proxies and mineralogy indicate moderate weathering and deposition under an arid palaeoclimate. The lack of clear lithostratigraphic markers and the sparse distribution of isolated outcrops in the basin prevent the relative age assessment of the facies associations. This study highlights the need for systematic high-precision geochronological studies, if possible from drill core samples, of the facies associations identified herein to constrain the stratigraphic relationships in the Oudtshoorn Basin. Until these reconstructed palaeoenvironments are in temporal isolation, the history of the Oudtshoorn Basin and its relationship to the other Mesozoic grabens and half grabens of the southern Cape remain elusive.